2008
DOI: 10.4103/0250-474x.43003
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective activity of <i> Ficus carica</i> leaf extract on rifampicin-induced hepatic damage in rats

Abstract: Shade dried leaves of Ficus carica were extracted using petroleum ether (60-80°) and tested for antihepatotoxic activity on rats treated with 50 mg/kg of rifampicin orally. The parameters assessed were serum levels of glutamic oxaloacetate transaminase, glutamic pyruvic transaminase, bilirubin and histological changes in liver. Liver weights and pentobarbitione sleeping time as a functional parameter were also monitored. There was significant reversal of biochemical, histological and functional changes induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 9 publications
3
31
0
Order By: Relevance
“…Our result revealed that INH/RIF administration to rats increased the levels of serum AST and ALT compared to the normal rats this was agreed by [38,39]. The reduction in the levels of these parameters toward the respective normal values by Moringa oleifera is an indication of the stabilization of plasma membranes as well as repair of hepatic tissue damage caused by INH/RIF [40].…”
Section: Discussionsupporting
confidence: 84%
“…Our result revealed that INH/RIF administration to rats increased the levels of serum AST and ALT compared to the normal rats this was agreed by [38,39]. The reduction in the levels of these parameters toward the respective normal values by Moringa oleifera is an indication of the stabilization of plasma membranes as well as repair of hepatic tissue damage caused by INH/RIF [40].…”
Section: Discussionsupporting
confidence: 84%
“…There was significant reversal of biochemical (glutamic oxaloacetate transaminase, glutamic pyruvic transaminase, bilirubin), histological and functional changes (pentobarbitione sleeping time) induced by rifampicin in rats treated by petroleum ether extract [116]. The hepato-protective action of Ficus carica leaf ethanolic extract was evaluated in hepatotoxicity induced by carbon tetrachloride (CCl 4 ) in mice.…”
Section: Nephro-and Hepato-protective Effectmentioning
confidence: 99%
“…Other species of Ficus viz. F. carica (Gond & Khadabadi, 2008), F. glomerata (Kubsad et al, 2008), and F. racemosa (Mandal et al, 1999) were found to have hepatoprotective activity. Based on this, an attempt has been made to evaluate the hepatoprotective effect of F. benghalensis.…”
Section: Introductionmentioning
confidence: 99%